Campus employment as a high-impact practice: relationship to academic success and persistence of first-generation college students - Savoca, Marianna, author; Feller, Richard, advisor; Peila-Shuster, Jacqueline J., advisor; Gloeckner, Gene W., committee member; Vigil, Patricia, committee member (Colorado State University. Libraries, 2016)
The double burden of spiraling costs and limited financial aid has prompted more college students to work more hours than ever. Yet, working more hours can be detrimental to students’ academic success and persistence, and first-generation college students are at even higher risk. While institutions cannot control off campus employment students choose, they do have opportunity to influence the content of jobs on campus. Campus jobs purposefully designed to provide a high-impact experience for students could potentially mitigate risk. The purpose of this study was to investigate how campus employment impacts academic success and persistence of first-generation college students, and compare differences in academic success and persistence of first-generation college students whose campus jobs were configured as high-impact practices with first-generation college students whose campus jobs were not, and make recommendations for practitioners. Archival datasets were collected from two institutions with a selection of campus jobs configured as high impact practices. The final sample included 1413 records of sophomores who had entered college as first-time, full-time freshmen, and worked on campus during their sophomore year. Regression analyses and factorial ANOVA were used to analyze the data. Results supported much of what has been shown in the literature about first-generation college students: they receive Pell, work more hours, earn lower GPAs and persist at lower rates. Results with respect to campus employment were inconclusive: type of campus job was not shown to be a significant individual predictor of either success measure, GPA or persistence. Yet, a statistically significant interaction of first-generation student status and type of campus job was found. While caution is recommended in interpreting such results, this interaction may stimulate different thinking for practitioners and researchers alike. Practitioners might consider the extent to which they could structure their campus jobs to include elements of high-impact practices; researchers may be encouraged to design studies of high-impact campus jobs and the extent to which they provide support for first-generation college students.